Mito e utopia em A Caverna, de José Saramago: o despertar da consciência - Santos, Luciana Alves dos (2010)
This research comes as a challenge made the criticism that, at one point, refers to the novel The Cave, by Jose Saramago, as a lower reading and pamphlet. The writer, in turn, engaged in intellectual discussions and presents on Social Forums, corroborates the statements to sharpen the criticism. Motivated by this clash of ideas, we began the search with a timely reflection on the work of writer and intellectual, with emphasis on theoretical reflections on Edward Said on the issue and seeking to study these two concepts in the perspective of approximation. The development of this work goes towards building relationships between the theoretical research and fictional text elected corpus of research. Thus, our analysis establishes a dialogue between Cipriano Algor, a character in the novel, and the figure of the writer-intellectual as metaphor in the text. The research hypotheses are tested, verifying the awakening of consciousness as a possible to look at for the poetic text and the concept of intellectuality that is built. The second case study relates to the symbolic presence of mythical and utopian spaces associated to the basic concept of literature in contemporary society. The contributions of this work for literary studies is in the possibility to discuss, once again, the dimension of the poetic word that, to if disclosing, leaves to escape his intellectuality and reflects what Said presents as notion of the responsibility, not politics, not social, but human. The novel, to retake in its narrative, the metaphor of clay, puts your reader as a character inserted in the text and proposes to him a scaling that makes reflect itself, parallel, as first and third person, doing an exercise of self-knowledge and self-criticism that offers a new form of existence